Households' probabilistic inflation expectations in high-inflation regimes - Becker, Christoph; Dürsch, Peter; Eife, Thomas A.; Glas, Alexander (FAU discussion papers in economics, 2023)
Central bank surveys frequently elicit households' probabilistic beliefs about future inflation. The responses provide only a coarse picture of inflation beliefs further away from zero. Using data from the Bundesbank household panel, we show that the current high-inflation environment induces respondents to allocate considerable probability to the rightmost open interval. This pile-up of probabilities negatively affects estimates of histogram moments and leads to a divergence between average expected inflation measured by probabilistic and point forecasts. The consistency of predictions can be improved by using an alternative design of the response scale that allows respondents to state more detailed beliefs for higher inflation ranges.